(untitled) - Alyeshmerni, Mansoor (New York, 1975)
Its purpose is not only to test the students' understanding of what they have read but to encourage them to make generalizations about language based on principles that they, as language users, know implicitly.
Keywords: Language and languages; Study and teaching